The synthesis of vinylphosphonate-linked RNA - Collis, Alana E.C. (2008)
An introductory chapter discusses the steric block, RNase H and RNA interference antisense mechanisms and the application of antisense nucleic acids as therapeutic agents. Examples of existing chemical modifications of the sugar and backbone regions of nucleic acids are given, followed by the introduction of the vinylphosphonate modification. The vinylphosphonate has previously been examined in DNA and has been synthesised by either Pd(0) catalysed cross-coupling of an H-phosphonate with a vinyl bromide, or by the cross-metathesis of a vinylphosphonate with a terminal olefin.